ANALYSIS OF QUALITY COSTS FOR STATISTICA QUALITY CONTROL PLANNING - N. Chiadamrong; C. Thaviwatanachaikul (Universitas Gadjah Mada, 2002)
Quality has become one or the most important force leading to organizational success and company growth in national and international markets. The return-on-investment from strong and effective quality programs is providing excellent profitability results in firms with effective quality strategies. Due to the wide variation in quality results, the search for the genuine keys to success in quality has become a matter of deep concern to management of companies. This paper suggests a way to quantifying quality costs. As a result, the appropriate quality strategies can be adjusted and set to match with each company situation based on the categorization of the quality costs suggested. This outcome can, then, be used as a guideline for manufactures in setting their suitable quality program, which establishes the proper balance between the costs and customer services.